2017
DOI: 10.1002/nau.23261
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic lumbopelvic stabilization for treatment of stress urinary incontinence in women: Controlled and randomized clinical trial

Abstract: After treatment, the DLS plus PFM exercise patients had results similar to those performing PFM exercises alone. However, the DLS plus PFM exercises were superior in the outcomes of incontinence severity, QoL, and impression of improvement in the post-90-day evaluation, showing longer lasting effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
1
5
0
2
Order By: Relevance
“…Physical therapy focused on a voluntary contraction of the pelvic floor muscles (PFMs) is considered to be the firstline approach to the prevention and therapeutic management of pelvic floor disorders. [1][2][3] Most training programs focus on aspects of PFM hypertrophy 4 and/or motor control, 5 with training approaches focused on maximal and rapid contractions. 3,4 In 1980, Caufriez hypothesized that because the PFMs are mainly composed of connective tissue 6 and tonic muscle fibers (type I), 7 they might benefit from training through automatic and tonic activation rather than maximal activation.…”
Section: Introductionmentioning
confidence: 99%
“…Physical therapy focused on a voluntary contraction of the pelvic floor muscles (PFMs) is considered to be the firstline approach to the prevention and therapeutic management of pelvic floor disorders. [1][2][3] Most training programs focus on aspects of PFM hypertrophy 4 and/or motor control, 5 with training approaches focused on maximal and rapid contractions. 3,4 In 1980, Caufriez hypothesized that because the PFMs are mainly composed of connective tissue 6 and tonic muscle fibers (type I), 7 they might benefit from training through automatic and tonic activation rather than maximal activation.…”
Section: Introductionmentioning
confidence: 99%
“…This idea has been supported by the study of Abreu et al, which did not find any differences in symptoms between the SUI group that performed dynamic lumbo-pelvic stabilization compared to the group performed PFM exercise after 5 weeks of training, whereas the stabilization exercise group showed better results in the evaluation after 90 days compared to the other group. 29 This study showed that in both groups, during the Valsalva maneuver and abdominal curl, the amount of bladder base descent did not change post-intervention compared to pre-intervention. In a study by McLean et al, the caudal displacement of the bladder neck, assessed by transperineal ultrasonography (TPUS), did not change during Valsalva maneuvers after PFM training in women with SUI.…”
Section: Interpretation Of Taus Datamentioning
confidence: 62%
“…Tonic activation in PFM rehabilitation should begin with tonic activity, as this is often incomplete [ 7 ]. This is different from many other programs for SUI which focus on strong PFM holds (up to 10 s) [ 38 ], and retraining of a tonic PFM action involves very gentle and prolonged muscle holds.…”
Section: Discussionmentioning
confidence: 78%